2015
DOI: 10.1097/igc.0000000000000321
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Chemotherapy Versus Primary Cytoreductive Surgery for Stage IV Uterine Serous Carcinoma

Abstract: Objective This study compares surgical and survival outcomes of women with stage IV uterine serous carcinoma (USC) treated with neoadjuvant chemotherapy (NAC) and interval cytoreduction to women treated with primary cytoreductive surgery (PCS) followed by adjuvant chemotherapy. Methods This retrospective dual cohort study included women diagnosed with stage IV USC at a single academic institution. Kruskal-Wallis and Fisher’s exact tests were used to compare demographics and surgical outcomes. Progression-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 21 publications
2
38
1
1
Order By: Relevance
“…Reported results in the treatment of uterine serous carcinoma are similar to those of ovarian cancer series, but with lower progression-free survival and overall survival rates. [21][22][23][24] In our series, overall survival was lower in the neoadjuvant chemotherapy group than the primary surgery group (20 months versus 27 months). This difference was statistically nonsignificant and is likely to be due to differences in demographics and patient selection, rather than treatment-related effects alone.…”
contrasting
confidence: 53%
See 1 more Smart Citation
“…Reported results in the treatment of uterine serous carcinoma are similar to those of ovarian cancer series, but with lower progression-free survival and overall survival rates. [21][22][23][24] In our series, overall survival was lower in the neoadjuvant chemotherapy group than the primary surgery group (20 months versus 27 months). This difference was statistically nonsignificant and is likely to be due to differences in demographics and patient selection, rather than treatment-related effects alone.…”
contrasting
confidence: 53%
“…Reported safety and effectiveness outcomes of neoadjuvant chemotherapy are comparable to those of primary cytoreductive surgery. [18][19][20][21][22][23][24] This study analysed outcomes for women with stage IV uterine serous carcinoma treated at the Queensland Centre for Gynaecological cancer, Queensland, Australia.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the utility of this approach, often in patients with serous histology because the pattern of disease spread is similar to that of ovarian cancer, in which the use of neoadjuvant chemotherapy is well described. In some cohorts, neoadjuvant chemotherapy has resulted in decreased operative time and hospital stay without worsening OS …”
Section: Therapy‐surgerymentioning
confidence: 99%
“…In some cohorts, neoadjuvant chemotherapy has resulted in decreased operative time and hospital stay without worsening OS. 83,84 Adjuvant Therapy…”
Section: Cytoreduction Surgery For Advanced or Recurrent Diseasementioning
confidence: 99%
“…Neoadjuvant chemotherapy is an alternative treatment approach for patients who are not suitable for primary surgical treatment. The role of neoadjuvant chemotherapy has been studied in various types of gynecologic malignancy including ovarian and high‐grade endometrial cancers; however, the effectiveness of neoadjuvant chemotherapy in UCS has not been studied likely due to the rarity of disease. Given that a substantial number of women with stage IV UCS are potentially poor candidates for primary surgical treatment, examining the utility of neoadjuvant chemotherapy prior to surgical treatment is of clinical value in the management of this disease.…”
Section: Introductionmentioning
confidence: 99%